Informing Conservation: Towards 14C Wiggle-Matching of Short Tree-Ring Sequences from Medieval Buildings in England. Issue 3 (30th August 2016) - Bayliss, A; Marshall, P; Tyers, C; Bronk Ramsey, C; Cook, G; Freeman, S P H T; Griffiths, S
Abstract: This study tested whether accurate dating by accelerator mass spectrometry (AMS) radiocarbon wiggle-matching of short tree-ring series ( 30 annual rings) in the Medieval period could be achieved. Scientific dating plays a central role in the conservation of historic buildings in England. Precise dating helps assess the significance of particular buildings or elements of their fabric, thus allowing us to make informed decisions about their repair and protection. Consequently, considerable weight, both financial and legal, can be attached to the precision and accuracy of this dating. Dendrochronology is the method of choice, but in a proportion of cases this is unable to provide calendar dates. Hence, we would like to be able to use 14 C wiggle-matching to provide a comparable level of precision and reliability, particularly on shorter tree-ring sequences ( 30 annual growth rings) that up until now would not routinely be sampled. We present the results of AMS wiggle-matching five oak tree-ring sequences, spanning the period covered by the vast majority of surviving Medieval buildings in England (about AD 1180–1540) when currently we have only decadal and bidecadal calibration data.